Gauging the Effects of Dependences on Control in Industrial Distribution Channels: Response Surface Approach - Kim,Steve; Hsieh,Ping-Hung (International Journal of Research in Marketing, 2006)
Keywords: Marketing; Supply Chain

Demand Generation in the IT Channel - Kim,Steve (Global Technology Distribution Council CEO Summit, 2004)
Keywords: Marketing

Interdependence and its Consequence in Distributor-Supplier Relationships: A Distributor Perspective Through Response Surface Approach - Kim,Steve; Hsieh,Ping-Hung (Journal of Marketing Research, 2003)
Interdependence and its consequences in marketing channels have received substantial research attention, but two issues remain unresolved. First, the validity of the extant methods to measure interdependence has not been verified, and those methods have not been contrasted. Second, the impact of interdependence on an outcome variable is difficult to analyze and its potential to provide managerial insight hampered. To address those gaps, the authors first review prior approaches. The review of prior approaches raises key methodological and theoretical issues in measuring interdependence and analyzing its impacts, including the additivity of distributor and supplier dependences for measurement of interdependence and the nonlinear functional forms of dependences for the impact of interdependence.The authors use the response surface approach (RSA) and derive three managerial insights that can be garnered from its use: interdependence for the highest (lowest) level of an outcome, directions for change in interdependence, and change in outcome when receding from the ideal combination. They apply RSA to the relationship between interdependence and three outcome variablesdistributor commitment, bilateral communication, and supplier controlin industrial distributor”supplier relationships and contrast it with previous methods. The empirical study results suggest that (a) distributors perceive differential effects of supplier dependence and distributor dependence on outcome variables and (b) highest magnitude and lowest asymmetry of interdependence do not lead to the highest distributor commitment or supplier control. From a distributor's standpoint, highest commitment and supplier control occur when distributor dependence is high and supplier dependence is modest. The following implications emerge: Distributor dependence and supplier dependence must be decoupled and treated separately. Distributor dependence can be encouraged and nurtured, while supplier dependence needs to be kept moderate. A supplier's too little or too great dependence on a distributor will deteriorate channel outcomes, at least from a distributor's point of view.
Keywords: Marketing; Supply Chain

Loyalty: The Influences of Satisfaction and Brand Community - McAlexander,Jim; Kim,Steve; Roberts,Scott (Journal of Marketing Theory and Practice, 2003)
This paper empirically explores the relative impacts of satisfaction, brand community integration, and consumer experience on customer loyalty as expressed by future purchase intentions and behavior. Data drawn from qualitative research and a survey of 1000 patrons of a Native American casino who indicate a willingness to engage in formal marketing relationships indicate that satisfaction yields to brand community integration as a key driver of loyalty. We discuss important implications of the findings for marketing theory and practice.
Keywords: Marketing

The Range of Self-Enforcing Agreement Use in Direct Business-to-Business Exchange Relationships - Kim,Steve; Stump,Rodney L.; Joshi,Ashwin W. (Winter AMA Marketing Educators’ Conference, 2003)
Keywords: Marketing

Relative Influence in Marketing Channels: An Empirical Test of the Influence of Distributor Specialized Investments in an Eastern Versus Western Culture - Kim,Steve; Stump,Rodney L.; Oh,Changho (Multicultural Marketing Conference, 2002)
Keywords: Marketing

Search and Collaboration: A Two-sided Buying Behavior in High Technology Markets - Kim,Steve; Kim,Hyunchul; Yamada,Tetsuya (Winter AMA Marketing Educators’ Conference, 2002)
Keywords: Marketing

Interpersonal Dependence and Efficiency of Interfirm Exchange: A Cross-National Study of Industrial Distributor ” Supplier Relationships - Kim,Steve (Winter AMA Marketing Educators’ Conference, 2001)
Keywords: Marketing

A Model of Self-Enforcing Agreement Use in Business-to-Business Exchange Relationships - Kim,Steve; Stump,Rodney L.; Joshi,Ashwin (IMP conference on Industrial Marketing, 2001)
Keywords: Marketing

A Cross-national Comparative Study on Interdependence Structure and Distributor Attitudes: Industrial Product Channels in the United States and Japan - Kim,Steve (AMA Winter Marketing Educators’ Conference, 2000)
Keywords: Marketing